Thermal decomposition of poly[3-phthalimido-2-hydroxypropyl methacrylate] - Coskun, MF; Demirelli, K; Coskun, M; Dogru, M (Elsevier Sci Ltd, 2002)
The thermal decomposition behaviour of poly(3-phthalimido-2-hydroxypropyl methacrylate) poly[PHPMA] was investigated by thermogravimetric analysis (TG) and by programmed heating of the polymer from ambient temperature to 500 degreesC under vacuum followed by product collection, and using IR spectra of partially degraded polymer. The cold ring fraction (CRF) of products volatile at degradation temperature but not at ambient temperature and the solid fraction trapped at -196 degreesC were identified by GC-MS, H-1 and C-13 NMR, FT-IR. The liquid fraction trapped at -196 degreesC was examined by H-1 NMR and FT-IR. Its gas phase was identified by FT-IR. On the degradation, the major products of CRF are the monomer (22.8%), N-(2,hydroxyallyl)phthalimide (21.01% by wt.) and N-(2,3-epoxypropyl)phthalimide (16.95% by wt.). The mechanism of thermal degradation, including formation of the major products, is discussed, Whether the polymer was affected by gamma- and beta-radiation was also tested. (C) 2002 Published by Elsevier Science Ltd.
Keywords: thermal degradation; phthalimide